1987
DOI: 10.1002/app.1987.070340102
|View full text |Cite
|
Sign up to set email alerts
|

Skin-core structure–fatigue behavior relationships for injection-molded parts of polypropylene. II. Morphology–fatigue behavior relationships

Abstract: SynopsisThe flexural fatigue properties were studied for PP injection-molded samples of different molecular weight and well-defined skin-core morphology (see Part I). It can be clearly seen that the crack initiation always OCCUR in the subskin layer of higher macromolecular orientation, and propagates towards the core. The mechanisos of cracking are discusoed on the basis of fatigue kinetic data and analytical meesurements on the stressed sections. The important influence of p d g conditions, essentially holdi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0

Year Published

1990
1990
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 0 publications
1
48
0
Order By: Relevance
“…Therefore the elucidation of the morphology and texture in the cross section of the mouldings is of great practical importance (cf. Trotignon & Verdu, 1987;Fujiyama, Wakino & Kawasaki, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore the elucidation of the morphology and texture in the cross section of the mouldings is of great practical importance (cf. Trotignon & Verdu, 1987;Fujiyama, Wakino & Kawasaki, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Such stiffening has previously been reported in conditioned polyamide-66 [32], but not in a polyacetal copolymer with similar glass transition temperature and crystallinity index [32]. Differential scanning calorimetry (DSC) measurements on virgin and fatigued specimens of conditioned polyamide-66 [32] and of polypropylene [49] previously indicated small increases in crystallinity related to fatigue-induced damage. However, DSC measurements on material taken from fatigued specimens of PA6 and PA6NC did not reveal a difference in crystallinity or crystalline forms.…”
Section: Discussionmentioning
confidence: 75%
“…Crystallites of the b form were found in the subskin layer of both the gate part and far part, because of the strong shear force occurring at this layer. An index A 110 characterizing the orientation of a-crystallites along flow direction was adopted [18]. (The determination of A 110 is based on the vanishing of the reflections (111) and (ð 131 þ 040Þ) in the equatorial measurement when the axes of the crystallites orient in the direction of flow.…”
Section: Orientation and Crystallinitymentioning
confidence: 99%
“…Because of the different thermomechanical history the melt undergoes, the injection-molded parts often show a hierarchical multilayered structure through the thickness [1][2][3][4][5][6][7][8][9]. For the universal semicrystalline polymer, Polypropylene (PP), this layered structure has been widely studied with its heterogeneous crystallization because of the shear and temperature gradient [10][11][12][13][14][15][16][17][18][19]. It has been reported that the injection-molded PP parts often show three distinct crystalline zones: a highly oriented nonspherulitic skin, a shear zone with molecular chains oriented essentially parallel to the injection direction, and a spherulitic core with essentially no preferred orientation, respectively [10].…”
Section: Introductionmentioning
confidence: 99%